A case of anomalous aortic origin of coronary arteries from the opposite sinus - Alessandra Tanzilli; Simone Griffo; Alessandra De Luca Vincenzo Capasso; Vincenzo Rossi; Marco Di Palma; Simone Calcagno; Francesco Panno; Riccardo Di Pietro; Pino Aisle; Francesco Versaci (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Anomalous origin of the left coronary artery from the right sinus is a relatively uncommon finding, with a reported prevalence of 0.02%-0.05% on angiographic studies [1]. Nevertheless, it is a leading cause of Sudden Cardiac Death (SCD) in young athletes and its clinic manifestations are strictly related to strenuous exertion. It is thought that the main mechanism of SCD relies on external compression of the abnormal coronary artery,